Strategic Use of AI Image Generators for Product Development and Market Expansion In The Bakery Business - Teodorine, Michelle; Indrawan, Genoveva Brigitta; Manuel, Michael; Kembau, Agung Stefanus (Journal of Accounting and Finance Management, 2024)
The evolution of Society 5.0, characterized by advanced technological integration, presents new opportunities for businesses to enhance operations and customer engagement. This study proposes the development of a comprehensive e-commerce website for Olson’s Patisserie, integrated with AI Image Generator technology, to improve digital sales and expand market reach. The proposal is informed by strategic insights from Porter's Five Forces, Fishbone analysis, and the VRIO framework, highlighting the need for enhanced digital marketing, technological integration, and operational efficiency. The website will serve as a central hub for digital marketing, leveraging Meta Ads to boost brand awareness and reach a broader audience. AI features will enable personalized cake design, enhancing customer satisfaction and loyalty through an interactive shopping experience. The platform will also streamline operations with a comprehensive dashboard for order management and real-time analytics, supporting agile decision-making and strategic planning. By addressing identified weaknesses and capitalizing on opportunities, the integration of AI technology into Olson’s Patisserie’s product development process promises to strengthen its competitive position, improve customer engagement, and drive business growth in the dynamic bakery industry.